2018
DOI: 10.1108/acmm-03-2017-1775
|View full text |Cite
|
Sign up to set email alerts
|

Corrosion inhibition of aluminium alloy by rhamnolipid biosurfactant derived frompseudomonassp. PS-17

Abstract: Purpose The purpose of this paper is to study the influence of rhamnolipid biosurfactant complex on the corrosion and the repassivation of a freshly cut Al-Cu-Mg aluminium alloy surface. Design/methodology/approach The electrochemical methods, supported by quantum-chemical calculations and scanning electron microscopy data, were used. Findings It was established that the rhamnolipid biosurfactant effectively inhibits corrosion of the alloy in synthetic acid rainwater. The efficiency of inhibition becomes s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(10 citation statements)
references
References 29 publications
0
10
0
Order By: Relevance
“…The shift of the phase angle θ maximum (Figure 9, curves 4 and 5) towards higher frequencies indicates the formation of a protective phosphate layer on the surface of the aluminium alloy [28]. The appearance of a second smaller peak on the phase angle dependencies 1, 2, 3 (Figure 9) in the frequency range of 50-200 Hz in addition to the first big one near 1 Hz indicates the presence of a defective surface film on aluminium alloy with insufficient protective properties.…”
Section: Resultsmentioning
confidence: 98%
“…The shift of the phase angle θ maximum (Figure 9, curves 4 and 5) towards higher frequencies indicates the formation of a protective phosphate layer on the surface of the aluminium alloy [28]. The appearance of a second smaller peak on the phase angle dependencies 1, 2, 3 (Figure 9) in the frequency range of 50-200 Hz in addition to the first big one near 1 Hz indicates the presence of a defective surface film on aluminium alloy with insufficient protective properties.…”
Section: Resultsmentioning
confidence: 98%
“…Zin [ 25 ] investigated the effect of rhamnolipid biosurfactant complexes on the corrosion and passivation of freshly cut aluminum–copper–magnesium aluminum alloy surfaces. It was demonstrated that the rhamnolipid biosurfactant effectively inhibited the corrosion of the alloy in synthetic acidic rainwater.…”
Section: Classification Of Biomass Corrosion Inhibitorsmentioning
confidence: 99%
“…Zin et al [59] studied the influence of surface-active rhamnolipid biocomplex produced by the Pseudomonas sp. PS-17 on the corrosion and the repassivation of a freshly cut Al-Cu-Mg aluminum alloy surface.…”
Section: Application Of Biosurfactants As Biocides: Examples From Thementioning
confidence: 99%
“…Bacillus species Lipopeptides Antagonistic effects against a broad spectrum of microorganisms [38,43] Bacillus amyloliquefaciens, Bacillus subtilis Peptide, lipopeptides Antagonistic effects against many fungal pathogens [69,70] Bacillus subtilis Surfactin Inhibit biofilm formed by Salmonella enterica, E. coli, and Proteus mirabilis [51] Pseudomonas sp. PS-17 Rhamnolipids Inhibit corrosion of alloy [59] Pseudomonas spp. Rhamnolipids Algicidal, anti-amoebal and zoosporicidal properties [47,49] Pseudomonas fluorescens Biosurfactant Inhibit corrosion of stainless steels [58] Pseudomonas stutzeri F01 Biosurfactant Antibacterial properties to corrosive bacterial strains [61]…”
Section: Biosurfactants Role Referencesmentioning
confidence: 99%